DEVELOPMENT OF BRAND IDENTITY AND PACKAGING FOR OTOP “KAE FARANG” PRODUCTS REFLECTING THE IDENTITY OF ARANYAPRATHET SCHOOL, SA KAEO PROVINCE - Iam-khong, Nuttaya; Tanvichan, Piyangkoon (Journal of Social Science and Cultural, 2025)
This research aimed to 1) Analyze problems, needs, and expectations for brand identity and packaging of OTOP “Kae Farang” products in Aranyaprathet District, Sa Kaeo Province, and 2) Develop brand identity and packaging for OTOP "Kae Farang" products that reflect the identity of Aranyaprathet School, Sa Kaeo Province. This study employed mixed methods research with purposive sampling of two groups: 1) 7 OTOP “Kae Farang” entrepreneurs, from whom data was collected through unstructured interviews, and 2) a brand and packaging evaluation group, using evaluation forms and satisfaction interviews. The findings revealed that: 1) Problems identified included the recently established OTOP not being widely recognized within the community at provincial or national levels, lack of knowledge in brand and packaging design, and challenges creating packaging that enhances marketing; and 2) Satisfaction evaluation of the brand and packaging design for OTOP “Kae Farang” products showed results in three parts: 1) For brand identity, experts selected design #2 through group consensus; 2) For banana flower tea with ginger packaging, experts determined it met the entrepreneurs’ requirements with a very high satisfaction level; and 3) For ginger Tuile cookie packaging, which included product information (address, telephone number, and Facebook contact), experts showed particular interest in the transparent round can packaging with protective seals that preserve quality, which aligned with entrepreneurs’ requirements.